Free Sex Behavior of Adolescents in Kendari City - Nabila, Jeihan (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
The condition of Indonesian youth is very alarming right now. This can be seen from the condition of some teenagers currently who tend to be more free and less attention to the moral values ââcontained in every action they do. The purpose of this study was to determine the phenomenon of free sex behavior in adolescents in Kendari city. The type of research used was qualitative with phenomenological approach. Selection of informants by using purposive sampling method. The results show the cause of adolescents performing free sex behavior is because undergoing a relationship dating for so long, performing the behavior on the basis of mutual love and demand from a boyfriend. Knowledge of adolescent about free sex behavior is to do sex before marriage, information obtained through school, internet, television media and from friend of mine. The process of free sex behavior by teenagers is at home girlfriend, in hotels, and in boarding house. The perceived consequences of having sex is losing virginity and becoming accustomed to such behavior and feeling addicted to wanting to try again. Influential so that adolescents to have free sex is teenage boyfriend and peers. According to teenagers if the surrounding community knows teenagers have had premarital sex then people will think bad and negative.